Debating diversity : analysing the discourse of tolerance - Blommaert, Jan (Routledge, 1998)
An eminently readable analysis on the rhetoric of the 'tolerant majority' - those who view themselves as being open to a diverse society; a rhetoric that is prevalent throughout the news media and political world.